ISUOG/ESGO Consensus Statement on ultrasound-guided biopsy in gynecological oncology - Fischerova, D; Planchamp, F; Alcázar, J L; Dundr, P; Epstein, E; Felix, A; Frühauf, F; Garganese, G; Haldorsen, I Salvesen; Jurkovic, D; Kocian, R; Lengyel, D; et al. (Ultrasound in obstetrics & gynecology, 2025)
The International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) with the European Society of Gynaecological Oncology (ESGO) jointly developed clinically relevant and evidence-based statements on performing ultrasound-guided biopsies in gynecological oncology. The objective of this Consensus Statement is to assist clinicians, including gynecological sonographers, gynecological oncologists and radiologists, to achieve the best standards of practice in ultrasound-guided biopsy procedures. ISUOG/ESGO nominated a multidisciplinary international group of 16 experts who have demonstrated leadership in the use of ultrasound-guided biopsy in the clinical management of patients with gynecological cancer. In addition, two early-career gynecological fellows were nominated to participate from the European Network of Young Gynae Oncologists (ENYGO) within ESGO and from ISUOG. The group also included a patient representative from the European Network of Gynaecological Cancer Advocacy Groups. The document is divided into six sections: (1) general recommendations; (2) image-guided biopsy (imaging guidance, sampling methods); (3) indications and contraindications; (4) technique; (5) reporting; and (6) training and quality assurance. To ensure that the statements are evidence-based, the current literature was reviewed and critically appraised. Preliminary statements were drafted based on this review of the literature. During a conference call, the whole group discussed each preliminary statement, and a first round of voting was carried out. The group achieved consensus on all 46 preliminary statements without the need for revision. These ISUOG/ESGO statements on ultrasound-guided biopsy in gynecological oncology, together with a summary of the evidence supporting each statement, are presented herein. This Consensus Statement is supplemented by detailed narrated videoclips presenting different approaches and indications for ultrasound-guided biopsy, a patient leaflet, and an extended version which includes a detailed review of the evidence. © 2025 The Authors. Published by John Wiley & Sons Ltd on behalf of The International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) and by Elsevier Inc. on behalf of the European Society of Gynaecological Oncology and the International Gynecologic Cancer Society.
Keywords: intervenční ultrasonografie; Consensus; společnosti lékařské; Image-Guided Biopsy; Genital Neoplasms, Female; nádory ženských pohlavních orgánů; lékařská onkologie; ultrazvukem navigovaná biopsie; gynekologie; lidé; Female; Societies, Medical; ženské pohlaví; Humans; Gynecology; konsensus; Medical Oncology; Ultrasonography, Interventional